Problem Solving Administration of Notary/PPAT’s Errors - Yuni Hanriani; Maryanto Maryanto (Sultan Agung Notary Law Review, 2020)
This study was appointed because of a problem that arose at PT bank BRI Syari’ah Semarang Branch Office, where there was an error in writing the financing agreement in the explanation of the principal deed. The problem was only discovered 1 year after the signing of the notarial financing agreement and the issuance of the mortgage rights by BPN and the customer with the status of a non-performing customer so that a guarantee auction would be executed. The problems raised in this study were: (1) What were the factors that caused errors in making SKMHT ?; (2) How is the function of the Notary Regional Supervisor in resolving the Notary's mistakes in making the wrong SKMHT Notarial Deed ?; (3) How are the efforts to resolve the wrong SKMHT that has been issued by BPN, without harming the parties? The research methodology used in this research is a sociological yuiridis approach, by paying attention to conditions in the field and linking them to the prevailing laws and regulations. Based on the results of research in the field, it is known that: (1) The factors that caused errors in making a Power of Attorney to impose Mortgage Rights (SKMHT) were: negligence in writing in Minuta which resulted in imperfect binding defects on matters that had been agreed between the two parties. parties, the lack of thoroughness between the parties in further examination of the results of the writing that has been made in the form of SKMHT deeds, and is due to excessive trust in their staff; (2) The function of the notary area supervisory board in examining and resolving problems in the field, also checks the physical minimum deeds of notaries. Viewed in an ideal level, it is necessary to separate the authority of the supervisory board. namely, the supervisory panel is more appropriate to supervise the behavior of a notary in carrying out the duties of a notary public or behavior that can interfere with the performance of the notary's duties; (3) Settlement measures taken by BRI Syari’ah and the notary concerned, is that the Bank asks the notary to be accountable by conducting a Renvoi by the Notary.